Effect of re-irradiation for painful bone metastases on urinary markers of osteoclast activity (NCIC CTG SC.20U). Issue 1 (April 2015) - Chow, Edward; DeAngelis, Carlo; Chen, Bingshu E.; Azad, Azar; Meyer, Ralph M.; Wilson, Carolyn; Kerba, Marc; Bezjak, Andrea; Wilson, Paula; Nabid, Abdenour; Greenland, Jonathan; Rees, Gareth; et al.
Abstract Purpose The NCIC CTG Symptom Control.20 randomized trial (SC.20) confirmed the effectiveness of re-irradiation to painful bone metastases. This companion study correlates urinary markers of osteoclast activity with response to re-irradiation, survival and skeletal related events (SREs). Methods Pain response was assessed using the International Consensus Endpoints. Urinary markers of bone turnover-pyridinoline (PYD), deoxypyridinoline (DPD), N-telopeptide (NTX), Alpha and Beta cross-laps of C-telopeptide (CTX)-before and 1 month after re-irradiation were correlated to response to re-irradiation and then to both, either or none of the initial and re-irradiation: frequent responders (response to both); eventual responders (response to re-irradiation only); eventual non-responders (response to initial radiation only), and absolute non-responders (no response to both). Results Significant differences between 40 responders and 69 non-responders to re-irradiation existed for PYD (p = 0.03) and DPD (p = 0.04) at baseline. When patients were categorized as frequent responders (N = 34), eventual responders (6), eventual non-responders (59) and absolute non-responders (10), the mean values of all markers in the absolute non-responders at baseline and the follow-up were about double those for the other three groups with statistically significant difference for DPD (p = 0.03) at baseline. Absolute non-responders had the worst survival. The few occurrences of the SREs did not allow meaningful comparisons among the groups. Conclusion There were significant differences between responders and non-responders to re-irradiation for PYD and DPD at baseline. The urinary markers in the absolute non-responders were markedly elevated at both baseline and follow-up with a statistically significant difference for DPD at baseline.